The marriage of psychology and law: testamentary capacity. Issue 4 (4th July 2019) - Zuscak, Simon; Coyle, Ian; Keyzer, Patrick; Machin, M. Anthony
Abstract : Banks v. Goodfellow [1870. LR 5 QB 549 (Eng.)] is almost 150 years old, yet still stands as authority for the principle that unsoundness of the mind will not rebut testamentary capacity where it does not affect the will itself. Readers of this journal would know that psychology has advanced greatly during this sesquicentenary, and yet the law relating to testamentary capacity has remained relatively stagnant. We review the present laws relating to decision-making for adults with impaired capacity, particularly in Queensland, and also review various models of gauging decision-making capacity in other jurisdictions. We argue that qualified experts should be enlisted to make determinations about testamentary capacity when questions of capacity arise. We also argue the case for the development of scientifically validated protocols to assess decision-making capacity in the testamentary context.